2014
DOI: 10.1371/journal.pone.0113317
|View full text |Cite
|
Sign up to set email alerts
|

Early Retinal Function Deficit without Prominent Morphological Changes in the R6/2 Mouse Model of Huntington’s Disease

Abstract: Huntington’s disease (HD) is an inherited neurodegenerative disorder that primarily affects the medium-size GABAergic neurons of striatum. The R6/2 mouse line is one of the most widely used animal models of HD. Previously the hallmarks of HD-related pathology have been detected in photoreceptors and interneurons of R6/2 mouse retina. Here we aimed to explore the survival of retinal ganglion cells (RGCs) and functional integrity of distinct retinal cell populations in R6/2 mice. The pattern electroretinography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 49 publications
3
32
0
Order By: Relevance
“…However, The HD group has been analysed as a whole, and also separated into Manifest HD and pre-manifest HD groups. p values have been given for comparisons between the complete HD group and control participants * Denotes significance J Neurol drosophila and mouse models of HD, present with severe neuropathology, including progressive disorganisation of the photoreceptor layer and retinal dysfunction suggesting that the retina may exhibit the same neuronal pathology as the rest of the brain [39,[42][43][44][45]. In our study, inspection of OCT images did not reveal any obvious photoreceptor abnormalities.…”
Section: Discussionmentioning
confidence: 47%
“…However, The HD group has been analysed as a whole, and also separated into Manifest HD and pre-manifest HD groups. p values have been given for comparisons between the complete HD group and control participants * Denotes significance J Neurol drosophila and mouse models of HD, present with severe neuropathology, including progressive disorganisation of the photoreceptor layer and retinal dysfunction suggesting that the retina may exhibit the same neuronal pathology as the rest of the brain [39,[42][43][44][45]. In our study, inspection of OCT images did not reveal any obvious photoreceptor abnormalities.…”
Section: Discussionmentioning
confidence: 47%
“…It is unclear whether the retina is affected in HD. Animal models using R6 mice suggested that there is an initial stage in which dysfunction of the photoreceptors, mainly cones, is observed, without any morphological changes (without evidence of significant cell loss) . This may be because of functional impairment of cone‐related proteins caused by huntingtin.…”
Section: Discussionmentioning
confidence: 99%
“…Although Knapp et al [18] report findings from a single case study, it is of note that reduced ERG amplitudes are in keeping with results from mouse models of Huntington's Disease [19]. Moreover, a key difference between the two studies is that whereas Knapp et al [18] report data from an unmedicated premanifest subject, Pearl et al [17] report data from a group of HD-manifest patients.…”
Section: The Retinamentioning
confidence: 99%